2017
DOI: 10.3892/ijmm.2017.3149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone and 17β-estradiol on angiotensin-induced changes in tyrosine kinase activity in the androgen-independent human prostate cancer cell line, DU145

Abstract: Angiotensin II (AngII), the main peptide of the renin‑angiotensin system (RAS), is involved in the proliferation of different types of cells, normal and pathological as well. The protein tyrosine kinases (PTKs) play an important role in the growth, differentiation and apoptosis of cells. AngII action depends on the hormonal milieu of the cell, and on sex steroid influence. Angiotensin 1‑7 (Ang1‑7), metabolite of AngII, shows opposite action to AngII in cells. The present study aimed to examine the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…At the same time, our data may be relevant to the experimental studies of steroid hormones action in vivo, studies with whole animals or (and particularly so) with cell cultures. Concentration of the hormones employed in such studies often reach a submillimolar or even millimolar range [ 29 , 30 , 31 , 32 , 33 ]. For example, in the paper of D’Ascenzo et al [ 29 ], the following IC 50% values are cited for inhibition of cell growth by anabolic steroides: testosterone, 100 µM; androstenedione, 375 µM; nandrolone, 9 µM; norandrostenedione, 500 µM; norandrostenediol, 6 mM.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, our data may be relevant to the experimental studies of steroid hormones action in vivo, studies with whole animals or (and particularly so) with cell cultures. Concentration of the hormones employed in such studies often reach a submillimolar or even millimolar range [ 29 , 30 , 31 , 32 , 33 ]. For example, in the paper of D’Ascenzo et al [ 29 ], the following IC 50% values are cited for inhibition of cell growth by anabolic steroides: testosterone, 100 µM; androstenedione, 375 µM; nandrolone, 9 µM; norandrostenedione, 500 µM; norandrostenediol, 6 mM.…”
Section: Discussionmentioning
confidence: 99%
“…No down-regulation in AT1 expression was observed in any prostate cancer line whereas a significant increase in expression was seen in the PC3 line. An earlier study presented that Ang1–7 can increase the protein level of the AT1 receptor in androgen-independent prostate cancer cells, and that this effect was attenuated by 17β-estradiol, not by testosterone 23 . Although the current study also evaluated the effect of Ang1–7 on the AT4 / IRAP receptor, its mRNA level was found to remain unchanged.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, while 17-β-estradiol partially reverses this effect, testosterone both disrupts the action of Ang1–7 and leads to an increase in PTK activity. Moreover, the application of PD19234, a specific AT2 receptor antagonist, resulted in the reversal of the changes triggered by testosterone 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Ang IV acted, at least partially, through AT2R, because addition of its blocker, PD123319, decreased inhibitory effect [83]. Domińska et al observed that steroid hormones, testosterone, and 17β-estradiol were capable of reversion of the action of Ang II and Ang 1-7, which decreased protein TK activity in the late-stage prostate cancer cell line-DU145 [84]. Ito et al noticed that inhibition of AT2R by its agonist, Compound 21 (C21), resulted in reduction of proliferation of prostate cancer cells and transgenic rat for adenocarcinoma of prostate (TRAP).…”
Section: Prostate Glandmentioning
confidence: 99%